Transcuticular calcium imaging as a tool for the functional study of insect odorant receptors - Mariette, Julia; Noël, Amélie; Louis, Thierry; Montagné, Nicolas; Chertemps, Thomas; Jacquin-Joly, Emmanuelle; Marion-Poll, Frédéric; Sandoz, Jean-Christophe (Frontiers in Molecular Neuroscience, 2023)
The primary actors in the detection of olfactory information in insects are odorant receptors (ORs), transmembrane proteins expressed at the dendrites of olfactory sensory neurons (OSNs). In order to decode the insect olfactome, many studies focus on the deorphanization of ORs (i.e., identification of their ligand), using various approaches involving heterologous expression coupled to neurophysiological recordings. The “empty neuron system” of the fruit fly Drosophila melanogaster is an appreciable host for insect ORs, because it conserves the cellular environment of an OSN. Neural activity is usually recorded using labor-intensive electrophysiological approaches (single sensillum recordings, SSR). In this study, we establish a simple method for OR deorphanization using transcuticular calcium imaging (TCI) at the level of the fly antenna. As a proof of concept, we used two previously deorphanized ORs from the cotton leafworm Spodoptera littoralis, a specialist pheromone receptor and a generalist plant odor receptor. We demonstrate that by co-expressing the GCaMP6s/m calcium probes with the OR of interest, it is possible to measure robust odorant-induced responses under conventional microscopy conditions. The tuning breadth and sensitivity of ORs as revealed using TCI were similar to those measured using single sensillum recordings (SSR). We test and discuss the practical advantages of this method in terms of recording duration and the simultaneous testing of several insects.